Global Civil Society 2004/2005. - Anheier, Helmut K., 1954- (Global Civil Society - Year Books., 2004)
Global Civil Society 2004-5 includes a wealth of data on globalisation, the rule of law, NGO growth, values and attitudes, governance, civil liberties and a chronology of the myriad protests, conferences and campaigns that are the sinews of global civil society.